'Football for Health'—a football-based health-promotion programme for children in South Africa: a parallel cohort study. Issue 8 (14th June 2010) - Fuller, Colin W; Junge, Astrid; DeCelles, Jeff; Donald, James; Jankelowitz, Ryan; Dvorak, Jiri
Abstract : Objectives: To develop, implement and assess an interactive, football-based health education programme for children in South Africa. Design: Prospective cohort study with control group. Setting: Two schools in Khayelitsha township, South Africa. Participants: 370 children making up two intervention groups (Grade 6: 125; Grade 7: 131) and one control group (Grade 7: 114). Intervention: Eleven 90 min sessions, each divided into two 45 min halves of Play Football (football skills) and Play Fair (health issues), each session focused on one specific health risk factor. Main outcome measures: Health knowledge using a 20-item questionnaire; coaches' attitudes towards their training programme using a 10-item questionnaire and children's attitudes towards the health education programme using a six-item questionnaire. Results: Children in the Grade 7 intervention group showed significant (p<0.05) increases in the proportion of correct responses for nine of the 20 health knowledge questions postintervention, and these increases were maintained at 3 months postintervention. The Grade 6 intervention group showed significant increases in the proportion of correct responses for 15 of the 20 health knowledge questions postintervention. The Grade 7 control group showed a significant increase in the proportion of correct responses to one of the 20 health knowledge questions post-Play Football sessions and nine of 20 questions post-Play Fair sessions. Over 90% of the children provided positive attitude responses to the health-education programme. Conclusions: The programme demonstrated that it was possible to implement a football-based health-education programme for children in Africa that achieved significant increases in health knowledge and that was also well received by participants.